Betanin, isolated from fruits of Opuntia elatior Mill attenuates renal fibrosis in diabetic rats through regulating oxidative stress and TGF-β pathway. (23rd February 2017) - Sutariya, Brijesh; Saraf, Madhusudan
Abstract: Ethnopharmacological relevance: The fruits of Opuntia elatior Mill are being used traditionally in different disease condition like diabetes, obesity, asthma, inflammatory disorders, and anemia. Betanin, a compound isolated from fruits of Opuntia elatior Mill has potent anti-oxidative and anti-inflammatory activity. Recent study from our lab indicated the protective effect of betanin against high glucose induced rat renal epithelial cell fibrosis and matrix accumulation, major features of diabetic nephropathy (DN). However the molecular mechanism of betanin in DN has not yet been fully elucidated. Aim of the study: The aim of the present study was to further investigate the anti-fibrotic mechanisms of betanin against streptozotocin (STZ) induced DN. Materials and methods: Betanin was isolated from fruits of Opuntia elatior Mill (Cactaceae) and structure was elucidated using spectroscopy (UV, IR, 1H-NMR and mass). STZ was injected intraperitoneally with single dose of 50 mg/kg for diabetes induction. In order to develop DN the animals were left in diabetes condition without any treatment during the following 4 weeks. Betanin (25, 50 and 100 mg/kg/day) and lisinopril (5 mg/kg/day, reference compound) were orally administered for 8 weeks after the induction of DN. Renal function, blood glucose, serum creatinine, blood urea nitrogen (BUN) and antioxidant enzyme activities in the kidney tissue were measured. Kidney tissue samples were used for glomerulosclerosis, tubulointerstitial fibrosis and morphometric studies. The expression of transforming growth factor-beta (TGF-β), type IV collagen, alpha-smooth muscle actin (α-SMA) and E-cadherin in kidney tissue were evaluated using reverse transcription-polymerase chain reaction, and immunohistochemistry. Results: Betanin was successfully isolated from fruits of Opuntia elatior Mill (Cactaceae) and purified by column chromatography. The results showed that betanin attenuated diabetic kidney injury by significantly inhibiting proteinuria, blood glucose, serum creatinine and BUN levels and restored antioxidant enzyme activities in kidney tissue. Histological studies exhibited that betanin treatment reduced the glomerular surface area, glomerulosclerosis and tubulointerstitial fibrosis. Furthermore, betanin modulated mRNA and protein expression of TGF-β, type IV collagen, α-SMA and E-cadherin in kidney. Conclusions: The results conclude that betanin can effectively suppress renal fibrosis in DN, and may slow down the progression to end-stage renal disease by regulating TGF-β signal pathway. Graphical abstract: